(untitled) (Fiep Bulletin - online, 2012)
Introduction: Excessive sun exposure and without proper prevention measures may result in serious effects on the immune system of workers, besides contributing to aging and the development of skin cancer, especially in people who work outdoors, as farmers. Objectives: To assess the knowledge and preventive measures of farmers regarding sun exposure. Methods: Descriptive study with quantitative approach carried out with 52 farmers from the Association of Small Farmers of Boa Esperança. Data was collected in May 2011 through a route of structured interview. Data was analyzed descriptively and presented in table. The research follows the guidelines of Resolution 196/96 CNS/MS. Results and Discussion: The results showed that the main preventive measures were presented in the wearing of hats and shirts with long sleeves and the exposure time was excessive. Most interviewees reported that the main source of information about skin cancer was the television and did not know the damage caused by sun exposure. Final Considerations: There is the need for campaigns in order to inform the effects of the sun on your skin, as well as damages caused by sun exposure, providing prophylaxis through health interventions aiming the health promotion and quality of life.